Ethnography Knowledge in Islamic Astronomy: Conceptual Framework of Ethno-Falak - Sulaiman, Nur Aida Athirah; Hassan, Shahir Akram (International Journal of Psychosocial Rehabilitation, 2020)
Until today, there has not been a clear use of the term ethno-falak in the study of falak. However, preliminary investigations on existing research reveal that a few similarities between the concepts of ethnoastronomy and ethno-falak have been discussed. This is mostly because the same definition of astronomy and falak has been used by a number of falak scholars. Ethnoastronomy is a specific term that defines the textual and ethnological study as well as the interpretation of ancient iconography for the purpose of reimagining the lifestyle, astronomical techniques, and religious ceremonies of a community. Ethnoastronomy study uses myths as its main source. On the other hand, falak encompasses various aspects, including religion, social, science and the dynamics of a society. Since falak is evidently a broader field, it follows that ethno-falak is a larger study compared to ethnoastronomy. However, what exactly is the conceptual framework of ethno-falak? Are there differences between ethno-falak and ethnoastronomy in the Western scholarship? This paper aims to answer these questions by first identifying the differences between ethno- falak and ethnoastronomy, and second, by analysing the fundamentals and elements of ethno-falak, which distinguish it from ethnoastronomy. Document review is chosen as the data collection method, and this research is done qualitatively. This study concludes that there are three criteria that differentiate ethno-falak from ethnoastronomy. Firstly, the sources for ethno-falak do not disagree with the Qur’an and hadith. Secondly, ethno-falak discusses the tauhid relationship between man and Allah. Thirdly, ethno-falak must include the connection between man and nature.